EDUCATION OF HEALTHY AND BALANCED FOOD IN THE MODERN BOARDING SCHOOL DARUSSALAM GONTOR CANTEEN IN CAMPUS 2 - Yuangga Kurnia Yahya; Damailuddin Rosyid; Raffi Afan Fadhilah; Kemal Aidil Pasya; Farchan Arifuddin (UNUSA Press, 2021)
The pattern of life in Islamic boarding schools requires a lot of energy and a balanced nutritional intake. However, with the existence of a management system for all business units by college and students, it was necessary to divide time for studying, teaching and helping the boarding school. Therefore, the provision of supporting food and drinks was not optimal and the nutrition intake and process cleanliness not guaranteed. The education activity for healthy and nutritionally balanced food was in the context of spreading insights into healthy, nutritious and clean food by the canteen managed by the student. It was to support the creation of balanced nutrition and support the growth of student who was early adolescents. The implementation strategy included slide presentations, discussions, and assistance to the canteen administrators. The activities of implementing services, managing food in the canteen, and paying attention to cleanliness intended to encourage changes in the diet of the student. In addition, this education was increasing the knowledge and sensitivity of canteen staff so that they can pay more attention to nutrition and health principles in the selection, process, and presentation of food and beverages.